Study on creating the three-dimensional shape of apparel by thermal bonding of thermoplastic polyurethane film and vacuum forming molding. (January 2020) - Yu, Qiuyu; Zhou, Feng; Jing, Lingxiao; Song, Jing; Xiang, Yi; Mo, Yu; Zhao, Yu
The shape of apparel is one of the most important elements in fashion design, for example, the three-dimensional shape of apparel can be quite creative and fashionable. The current technologies for creating the three-dimensional shape of apparel are many, but have their limitations in dealing with various fabrics, particularly light and soft fabrics. This article presents a new method to rapidly create three-dimensional shape of apparel for avoiding the aforementioned disadvantages. The method combines thermal bonding of thermoplastic polyurethane film and vacuum forming. In this study, 12 kinds of commercial fabrics were selected and then tested. All these fabrics were first bonded to thermoplastic polyurethane film and then rapidly applied to the vacuum forming machine to form the three-dimensional mold-like shape. This research analyzed the factors of molding a fabric to a good three-dimensional shape of apparel and the relative tests to be carried out for validating its stability for the selected fabric samples. There are two main contributions of this study. The first is to propose a more effective method for three-dimensional shape of apparel in fashion design. The second is to provide useful information for fabric selection and determination of bonding temperature in molding.